2008
DOI: 10.1196/annals.1434.015
|View full text |Cite
|
Sign up to set email alerts
|

The Placental Syncytium and the Pathophysiology of Preeclampsia and Intrauterine Growth Restriction

Abstract: Preeclampsia is associated with an increased release of factors from the placental syncytium into maternal blood, including the antiangiogenic factors soluble fms-like tyrosine kinase-1 and soluable endoglin, the antifibrinolytic factor plasminogen activator inhibitor-1, prostanoids, lipoperoxides, cytokines, and microparticles. These factors are suggested to promote maternal endothelium dysfunction and are associated with placental damage in pregnancies also complicated with intrauterine growth restriction (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…An excessive deposition of fibrin may disrupt the exchange of gas and nutrients between the maternal and fetal circulations in the intervillous space, accounting for some of the complications of preeclampsia [43]. Guller et al hypothesized that the excessive fibrin deposition in conjunction with the hypoxia-associated apoptosis/necrosis of syncytiotrophoblasts found in preeclampsia may produce the severe fetal outcomes and maternal symptoms that are associated with the disease [73]. Thus, plasminogen activator inhibitors could be a useful biomarker for the prediction of preeclamptic pregnancy outcome [72].…”
Section: Trophoblastic Fibrin Depositionmentioning
confidence: 99%
“…An excessive deposition of fibrin may disrupt the exchange of gas and nutrients between the maternal and fetal circulations in the intervillous space, accounting for some of the complications of preeclampsia [43]. Guller et al hypothesized that the excessive fibrin deposition in conjunction with the hypoxia-associated apoptosis/necrosis of syncytiotrophoblasts found in preeclampsia may produce the severe fetal outcomes and maternal symptoms that are associated with the disease [73]. Thus, plasminogen activator inhibitors could be a useful biomarker for the prediction of preeclamptic pregnancy outcome [72].…”
Section: Trophoblastic Fibrin Depositionmentioning
confidence: 99%
“…Understanding of it physiopathology remains unresolved, with symptoms disappearing after the delivery of the baby. Numerous studies have demonstrated an increased apoptosis level of placental villous trophoblasts in pregnancies complicated by pre‐eclampsia . The Fas receptor (Fas) and Fas ligand (FasL) system is an important extrinsic pathway implicated in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated an increased apoptosis level of placental villous trophoblasts in pregnancies complicated by pre-eclampsia. [2][3][4] The Fas receptor (Fas) and Fas ligand (FasL) system is an important extrinsic pathway implicated in apoptosis. During normal pregnancy, placental trophoblasts expressing FasL interact with Fas on activated T lymphocytes, which leads to T cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that dysregulation of the Fas/FasL signaling system in villous trophoblasts occurs in association with preeclampsia [23]; the Fas/FasL ratio increased in preeclamptic villi [24], and sera from preeclamptic women decreased trophoblast viability while increasing trophoblast sensitivity to Fas-mediated apoptosis [25]. It is of note, that in a recent study we presented a novel methodology in which laser capture microdissection (LCMD) followed by Western blotting was used to assess levels of syncytial Fas ligand (FasL) [26], suggesting that this technique may be used to elucidate changes in syncytial protein expression that occurs in preeclampsia and IUGR.…”
Section: Introductionmentioning
confidence: 99%